Applications of Contractive-like Mapping Principles to Fuzzy Equations - Nieto, Juan J.; Rodríguez López, Rosana (Revista Matemática Complutense, 2006)
We recall a recent extension of the classical Banach fixed point theorem to partially ordered sets and justify its applicability to the study of the existence and uniqueness of solution for fuzzy and fuzzy differential equations. To this purpose, we analyze the validity of some properties relative to sequences of fuzzy sets and fuzzy functions.